ANALISIS PENDAPATAN USAHA WARUNG MAKAN DI KAWASAN WISATA KULINER SIRING LAUT KOTABARU - Rika Sylvia (Jurnal Ekonomi dan Manajemen, 2018)
The purpose of this research is to analyze the amount of income of food stalls in the area of culinary tourism Kotabaru regency. The type of research used is descriptive quantitative with sampling using purposive sampling, while the sample is as much as 7 owners of food stalls. Data Analysis Technique used is cost analysis, business income analysis, and analysis of revenue and expense balance. The results of this study indicate that only 3 food stalls that have more than 1 R / C, namely Warung Lili, Kedai HBS, and Dapur Zaliquq, while Warung Mamanda, Kedai Zhie, New Kaero Cafe, and Cafe 4 Saudara show the value of R / C less than 1.